Rekrutmen Karyawan dan Kinerja Karyawan: Sistematik Tinjauan Literatur - Heida Ifkari Safitri; Sopiah Sopiah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The purpose of this analysis is to analyze employee recruitment and employee performance. This research uses the systematic literature review method. The data source obtained from Scopus was 313 for the 2019–2023 period, and we continued with the exclusion and inclusion criteria to obtain 46 journals that were reviewed. The results of this research state that digitalization technology makes the employee recruitment process easier, one of which is distributing advertisements on the company's official website. The recruitment system needs to have a good framework to attract quality employees. Employee performance is also influenced by individual and organizational factors; therefore, companies need to consider the age and experience factors of a prospective employee. The company's strategy for its employees is also very important to increase employee productivity.